1995
DOI: 10.1136/hrt.73.1.32
|View full text |Cite
|
Sign up to set email alerts
|

QT dispersion and components of the QT interval in ischaemia and infarction.

Abstract: Objective-To evaluate changes in QT dispersion and components of the QT interval in patients admitted with unstable angina and acute myocardial infarction and to study the dynamics of these changes in patients with infarction. (Br Heart J 1995;73:32-36)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
1
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(127 citation statements)
references
References 10 publications
8
112
1
6
Order By: Relevance
“…In our study, in addition to QTD parameters, we also investigated the value of QTDR, which was found superior to QTcD in the diagnosis of ventricular fibrillation, and QTcD and QTDR differences at rest and on exercise to diagnose CAD and predict its extent in women. 13 Since up to now no absolute cut-off value has been obtained from the studies, we determined the cut-off value according to the lowest values in 95% CI from the group of patients with the least extensive CAD. Thus, exercise QTD, QTcD, QTDR, QTcDD, and QTDRD cut-off values were calculated as 40 ms, 60 ms, 10%, 15 ms, and 5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, in addition to QTD parameters, we also investigated the value of QTDR, which was found superior to QTcD in the diagnosis of ventricular fibrillation, and QTcD and QTDR differences at rest and on exercise to diagnose CAD and predict its extent in women. 13 Since up to now no absolute cut-off value has been obtained from the studies, we determined the cut-off value according to the lowest values in 95% CI from the group of patients with the least extensive CAD. Thus, exercise QTD, QTcD, QTDR, QTcDD, and QTDRD cut-off values were calculated as 40 ms, 60 ms, 10%, 15 ms, and 5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The QTDR was obtained by the formula of (QTD/RR-ms) ϫ 100. 13 An observer blinded to the clinical and angiographic findings for the patients measured the QT intervals. By taking the differences between QTD, QTcD, and QTDR at rest and at peak exercise, the QTD difference (QTDD), QTcD difference (QTcDD), and QTDR difference (QTDRD) were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since QT dispersion varies greatly in the acute phase of myocardial infarction, 4,14) Glancy, et al have pointed out that the time of measurement should be taken into consideration when interpreting QT dispersion data. 4) Gabrielli, et al 20) reported that QT dispersion was increased soon after infarction and then decreased again after ten days, although not all patients showed improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Above all, an association between QT dispersion and fatal arrhythmias has frequently been reported. QT dispersion is increased in patients with ventricular tachycardia or those who develop ventricular tachycardia and ventricular fibrillation during the acute phase of myocardial infarction, [14][15][16][17][18] and it has been suggested that increased QT dispersion is the substrate for ventricular arrhythmias. 8) In a study investigating the association between reentrant ventricular tachyarrhythmias and QT dispersion after myocardial infarction, Perkiomaki, et al 16) found that the maximum QT interval was significantly longer in patients with ventricular tachycardia than in patients without arrhythmia or normal subjects, and that QT dispersion was an independent predictor of prognosis for the patient group according to multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%